2007
DOI: 10.1681/asn.2006070772
|View full text |Cite
|
Sign up to set email alerts
|

Glycated Albumin Is a Better Glycemic Indicator than Glycated Hemoglobin Values in Hemodialysis Patients with Diabetes

Abstract: The significance of glycated albumin (GA), compared with casual plasma glucose (PG) and glycated hemoglobin (HbA 1c ), was evaluated as an indicator of the glycemic control state in hemodialysis (HD) patients with diabetes. The mean PG, GA, and HbA 1c levels were 164.5 ؎ 55.7 mg/dl, 22.5 ؎ 7.5%, and 5.85 ؎ 1.26%, respectively, in HD patients with diabetes (n ‫؍‬ 538), which were increased by 51.5, 31.6, and 17.7%, respectively, compared with HD patients without diabetes (n ‫؍‬ 828). HbA 1c levels were signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
415
6
13

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 470 publications
(458 citation statements)
references
References 26 publications
18
415
6
13
Order By: Relevance
“…First, the reference range for GA was determined as three times the reference range for HbA 1c in the present study. Although this was based on the results from several previous reports 8 , the actual conversion coefficient between GA and HbA 1c might be smaller than 3.0. A slight change in the GA level for categorizing prediabetes/diabetes would seriously affect the projected number of such persons.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…First, the reference range for GA was determined as three times the reference range for HbA 1c in the present study. Although this was based on the results from several previous reports 8 , the actual conversion coefficient between GA and HbA 1c might be smaller than 3.0. A slight change in the GA level for categorizing prediabetes/diabetes would seriously affect the projected number of such persons.…”
Section: Discussionmentioning
confidence: 97%
“…The reference range for GA on which diabetes is categorized has not yet been officially determined, therefore reports from several studies that dealt with the correlation between HbA 1c and GA were referenced. It was found that most studies concentrated on an average ratio of 3:1 for the GA:HbA 1c ratio 8 . The JRCS therefore adopted a tentative value for the reference range for GA that was three times the reference range for HbA 1c (Japan Diabetes Society value) 9 .…”
Section: Methodsmentioning
confidence: 99%
“…30,46,47 Plasma 1,5-anhydroglucitol (1,5-AG) is a naturally occurring dietary polyol that has been proposed as a measure of glycemic control. Renal reabsorption of 1,5-AG is competitively inhibited by glucose.…”
Section: Alternatives To Using A1cmentioning
confidence: 99%
“…Anemia, which results from a short erythrocyte lifespan, theoretically suppresses HbA1c levels. Therefore, some studies have suggested that the HbA1c level is not the optimal index for assessing glycemic control in diabetic dialysis patients and those with advanced chronic kidney disease who receive erythropoietin [17][18][19]. By increasing the proportion of young erythrocytes in the blood, both anemia and erythropoietin can falsely lower the HbA1c level, leading to a false negative diagnosis of hyperglycemia.…”
Section: Adverse Effects and Other Metabolic Effectsmentioning
confidence: 99%